The Missed symptoms of behjet’s disease - Altaha, lama H. (Journal of the Faculty of Medicine Baghdad, 2021)
AbstractObjectives: Behçet's disease is a systemic chronic proinflammatory vascular disease .this study wants to describe more details of patients with Behçet’s disease in iraq.Methods: Any patient with suspected or diagnosed  Behçet’s  disease attending centre of dermatology/behjet unit , 2017-  2018.A total 47 patients ,Full history and examination were taken.Percentage of complains were calculated.Results: 37 were females and 10 were males , Age of patients ranged from (11-63) years.Pethargy test was negative in 13 patients , positive in 15 ,21 had negative family history and 9 had positive .They complain from Malaise , oral ulcer, genital ulcer, unexplained fever ,20 symptoms began from childhood ,decreased hearing,eye complain, dysphagia , dyspnea ,headache ,  memory problems, depression , muscle contraction, peripheral paresthesia , joint complains, sleep disturbances and  renal problems.Conclusion:  describes new symptoms can help in diagnosis of behjet’s disease .